PENGARUH STRUKTUR KEPEMILIKAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DENGAN TIPE INDUSTRI TIPE INDUSTRI SEBAGAI VARIABEL MODERATING - RINI HIDAYAH; M Fitrayudi (Neraca, 2015)
The aim of this research is to get an empirical evidence about the impact of ownership structure; managerial ownership, institutional ownership, and foreign ownership on corporate social responsibility disclosure with industry type as a moderating variable. This research used Corporate Social Disclosure Index (CSDI) as a measure of CSR disclosure,based on indicators from Global Reporting Initiatives (GRI). The sampels of this research are 120 manufacture firms listed in Indonesian Stock Exchange (IDX) at 2013 with purposive sampling technique. The results show that managerial and institutional ownership do not have significant effect on CSR Disclosure ,but foreign ownership have significant effect on CSR Disclosure.Industry type as moderating variables can not affect the relationship between managerial ownership, institutional ownership, foreign ownership and CSR disclosure.